ECONOMETRIC ANALYSIS FOR THE IMPACT OF THE REAL EFFECTIVE EXCHANGE RATE ON THE JORDANIAN ECONOMY - Alawin, Mohammad; Sawaie, Khalid; Al-Omar, Ibrahim; Al-Hamdi, Mohaned (European Scientific Journal, ESJ, 2013)
This study tests the relationship between the real effective exchange rate and GDP in Jordan through the aggregate demand-aggregate supply theoretical framework. This study used the method â€œFully Modified OLSâ€, which is a one to estimate cointegration. The advantage of this method is in its ability to solve the problems of autocorrelation and biased parameters. The results showed that the appreciation of the real effective exchange rate does not reflect or nullify the international competitiveness of Jordanian goods as the traditional theory suggests. This means Jordan should continue maintaining stable real exchange rate. The results also showed the efficiency of using the narrow definition of money (M1) as an important monetary policy tool. However, it was shown that M1 is a more effective tool rather than the broad definition of money (M2).